SUBJECTIVE WELL-BEING (KESEJAHTERAAN SUBJEKTIF) DAN KEPUASAN KERJA PADA STAF PENGAJAR (DOSEN) DI LINGKUNGAN FAKULTAS PSIKOLOGI UNIVERSITAS DIPONEGORO - Ariati, Jati (Jurnal Psikologi, 2010)
The research is aimed to determine the correlation between job satisfaction, need for achievement, and dispositional resistance to change in a sample of 224 Diponegoro University lectures. The participants/ subjects are given three scales: job satisfaction scale, need for achievement scale and dispositional resistance to change scale. The results show a significant negative correlation between job satisfaction, need for achievement and dispositional resistance to change. The contribution of job satisfaction and need for achievement in predicting dispositional resistance to change is 24.9%.Kata kunci: subjective well-being, kepuasan kerja, dosenPermalink :